GAMBARAN KLINIS DAN ELEKTRONEUROGRAFI NEUROPATI ULNA DISTAL PADA PASIEN SINDROM TEROWONGAN KARPAL DI RUMAH SAKIT CIPTO MANGUNKUSUMO - Irfan Taufik*, Manfaluthy Hakim*, Fitri Octaviana*, Joedo Prihartono** (NEURONA, 2011)
INTRODUCTION SEVERAL STUDIES HAVE BEEN REPORTED IN ULNAR INVOLVEMENT CARPAL TUNNEL SYNDROME CTS THERE WAS ALSO SOME RESEARCHES CTS IN INDONESIA BUT THERE IS NO STUDY SHOWED CORRELATION BETWEEN CTS AND ULNAR NEUROPATHY AT THE WRIST THEREFORE THIS STUDY CAN BE A PRELIMINARY DATA TO EXPLORE ULNAR INVOLVEMENT IN CTS PATIENTS